FOLLOW-UP IN THE FORMATION OF INDEPENDENT SKILLS EDUCATIONAL ACTIVITIES OF STUDENTS OF THE PEDAGOGICAL UNIVERSITY ORGANIZATIONAL, OPERATIONAL AND SUBJECT LEVEL (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the problem concerning existing possibilities of pedagogical influence while forming students' self-directed educational activities skills in Pedagogical University on organizational, functional, and subjective levels.